Outcome of Infants Younger Than 1 Year With Acute Lymphoblastic Leukemia Treated With the Interfant-06 Protocol: Results From an International Phase III Randomized Study - Pieters, Rob; De Lorenzo, Paola; Ancliffe, Philip; Aversa, Luis Alberto; Brethon, Benoit; Biondi, Andrea; Campbell, Myriam; Escherich, Gabriele; Ferster, Alina; Gardner, Rebecca A; Kotecha, Rishi Sury; Lausen, Birgitte; et al. (Journal of clinical oncology, 2019)
PURPOSE: Infant acute lymphoblastic leukemia (ALL) is characterized by KMT2A (MLL) gene rearrangements and coexpression of myeloid markers. The Interfant-06 study, comprising 18 national and international study groups, tested whether myeloid-style consolidation chemotherapy is superior to lymphoid style, the role of stem-cell transplantation (SCT), and which factors had independent prognostic value. MATERIALS AND METHODS: Three risk groups were defined: low risk (LR): KMT2A germline; high risk (HR): KMT2A-rearranged and older than 6 months with WBC count 300 × 109/L or more or a poor prednisone response; and medium risk (MR): all other KMT2A-rearranged cases. Patients in the MR and HR groups were randomly assigned to receive the lymphoid course low-dose cytosine arabinoside [araC], 6-mercaptopurine, cyclophosphamide (IB) or experimental myeloid courses, namely araC, daunorubicin, etoposide (ADE) and mitoxantrone, araC, etoposide (MAE). RESULTS: A total of 651 infants were included, with 6-year event-free survival (EFS) and overall survival of 46.1% (SE, 2.1) and 58.2% (SE, 2.0). In West European/North American groups, 6-year EFS and overall survival were 49.4% (SE, 2.5) and 62.1% (SE, 2.4), which were 10% to 12% higher than in other countries. The 6-year probability of disease-free survival was comparable for the randomized arms (ADE+MAE 39.3% [SE 4.0; n = 169] v IB 36.8% [SE, 3.9; n = 161]; log-rank P = .47). The 6-year EFS rate of patients in the HR group was 20.9% (SE, 3.4) with the intention to undergo SCT; only 46% of them received SCT, because many had early events. KMT2A rearrangement was the strongest prognostic factor for EFS, followed by age, WBC count, and prednisone response. CONCLUSION: Early intensification with postinduction myeloid-type chemotherapy courses did not significantly improve outcome for infant ALL compared with the lymphoid-type course IB. Outcome for infant ALL in Interfant-06 did not improve compared with that in Interfant-99.
Keywords: zárodečné mutace; Myeloid-Lymphoid Leukemia Protein; Germ-Line Mutation; Cyclophosphamide; akutní lymfatická leukemie; histonlysin-N-methyltransferasa; Female; Infant; mitoxantron; Mitoxantrone; novorozenec; výsledek terapie; genová přestavba; ženské pohlaví; cytarabin; přežití bez známek nemoci; daunomycin; lidé; Infant, Newborn; Treatment Outcome; míra přežití; Antineoplastic Combined Chemotherapy Protocols; Cytarabine; Mercaptopurine; protokoly protinádorové kombinované chemoterapie; Histone-Lysine N-Methyltransferase; etoposid; Male; kojenec; Daunorubicin; Survival Rate; Disease-Free Survival; Gene Rearrangement; Precursor Cell Lymphoblastic Leukemia-Lymphoma; mužské pohlaví; Etoposide; merkaptopurin; cyklofosfamid; protoonkogenní protein MLL; Humans